Simple, Low-Cost Detection of Candida parapsilosis Complex Isolates and Molecular Fingerprinting of Candida orthopsilosis Strains in Kuwait by ITS Region Sequencing and Amplified Fragment Length Polymorphism Analysis - Asadzadeh, Mohammad; Ahmad, Suhail; Hagen, Ferry; Meis, Jacques F.; Al-Sweih, Noura; Khan, Ziauddin (PloS one, 2015)
Candida parapsilosis has now emerged as the second or third most important cause of healthcare-associated Candida infections. Molecular studies have shown that phenotypically identified C. parapsilosis isolates represent a complex of three species, namely, C. parapsilosis, C. orthopsilosis and C. metapsilosis. Lodderomyces elongisporus is another species phenotypically closely related to the C. parapsilosis-complex. The aim of this study was to develop a simple, low cost multiplex (m) PCR assay for species-specific identification of C. parapsilosis complex isolates and to study genetic relatedness of C. orthopsilosis isolates in Kuwait. Species-specific amplicons from C. parapsilosis (171 bp), C. orthopsilosis (109 bp), C. metapsilosis (217 bp) and L. elongisporus (258 bp) were obtained in mPCR. Clinical isolates identified as C. parapsilosis (n = 380) by Vitek2 in Kuwait and an international collection of 27 C. parapsilosis complex and L. elongisporus isolates previously characterized by rDNA sequencing were analyzed to evaluate mPCR. Species-specific PCR and DNA sequencing of internal transcribed spacer (ITS) region of rDNA were performed to validate the results of mPCR. Fingerprinting of 19 clinical C. orthopsilosis isolates (including 4 isolates from a previous study) was performed by amplified fragment length polymorphism (AFLP) analysis. Phenotypically identified C. parapsilosis isolates (n = 380) were identified as C. parapsilosis sensu stricto (n = 361), C. orthopsilosis (n = 15), C. metapsilosis (n = 1) and L. elongisporus (n = 3) by mPCR. The mPCR also accurately detected all epidemiologically unrelated C. parapsilosis complex and L. elongisporus isolates. The 19 C. orthopsilosis isolates obtained from 16 patients were divided into 3 haplotypes based on ITS region sequence data. Seven distinct genotypes were identified among the 19 C. orthopsilosis isolates by AFLP including a dominant genotype (AFLP1) comprising 11 isolates recovered from 10 patients. A rapid, low-cost mPCR assay for detection and differentiation of C. parapsilosis, C. orthopsilosis, C. metapsilosis and L. elongisporus has been developed.